Design of an IoT‑Based Maggot Cultivation System with Integrated Temperature, Humidity Monitoring and Automatic Feeding - Aga Riyanda; Mazlina Abdul Majid; Christian Manalu; Biuty Hanna Cristin Pakpahan; Alfi Syahri Ramadhan (Politeknik Negeri Medan, 2026)
Organic waste accumulation remains a major environmental challenge in many developing countries, including Indonesia. Black Soldier Fly (BSF) larvae or maggots have gained attention as an effective biological agent for converting organic waste into high-value biomass. However, conventional maggot cultivation often faces challenges in maintaining optimal environmental conditions and ensuring consistent feeding schedules. This study aims to design and develop an Internet of Things (IoT)-based maggot cultivation system that integrates real-time temperature and humidity monitoring with an automated feeding mechanism. The system utilizes an ESP32 microcontroller, DHT22 temperature–humidity sensor, MG996R servo motor, relay module, and a 16×2 LCD display. Data from environmental monitoring are transmitted to the Blynk platform, allowing users to monitor and control the system remotely through a smartphone application. Experimental testing was conducted during one maggot growth cycle to evaluate system performance. Results indicate that the system successfully maintained temperature within the optimal range of 28–34 °C and humidity between 64–70 %. The automated feeding system operated according to the programmed schedule without failure. Compared to conventional cultivation methods, the IoT system increased maggot biomass production by approximately 24.5 % and reduced mortality rates by about 50 %. These findings demonstrate that the proposed system can improve efficiency, reduce manual intervention, and support sustainable organic waste management.